Sophie Hernandez: capstone - Hernandez, Sophie, artist (Colorado State University. Libraries, 2022)
The artist's statement: As a person and an artist, I strongly believe in the power of creativity as a means of social justice, change, and hope for a better future. My work mainly focuses on bringing forth the stories and lived experiences of the oppressed, and educating others on what it means to be an ally, or to fight for a better world. Being a Latina living in the United States, these issues surrounding fundamental change ring home for me: I do not want to see future generations fight through what I have had to fight through. I truly believe this work is my purpose, and my place in the art world. I mainly use traditional materials such as acrylic paint, pen and ink, and marker, but I also dabble in photography and I am also well versed in Adobe products such as Illustrator and Photoshop. I strive to make my work as understandable and simplistic as possible, while speaking essential messages. Part of my process contains some research on the specific topic I want to create on, such as racism, human rights, and political issues, and figuring out exactly how I want to convey my messages. As a whole, my work represents my specific style as well as the importance of fundamental change, and the power of art in the process of change.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design